'Welcome to the Online Discussion Group': A Diagnostic Framework for Teachers - Kristina Love; Merle Isles (The Australian journal of language and literacy, 2006)
State and national curriculum authorities are increasingly encouraging students and teachers to use asynchronous online discussions to communicate both with known and unknown participants. In this paper, we offer a contribution towards the development of a framework that may help teachers design and manage those online discussions concerned with expressing ideas and discussing alternative views about texts in subject English.